ANALISIS KAWASAN BENCANA LONGSOR MENGGUNAKAN FUZZY LOGIC DI KECAMATAN SITUJUAH LIMO NAGARI KABUPATEN LIMA PULUH KOTA TAHUN 2015-2020 - Fadhilla Oktari; ahyuni ahyuni (JURUSAN GEOGRAFI FIS UNP, 2021)
This study aims to analyze the landslide hazard in Situjuah Limo Nagari District, Lima Puluh Kota Regency. The research method used is quantitative research. The data used are secondary data using fuzzy logic methods. The results of this study are 2 classifications of landslide vulnerability, namely moderate landslide hazard with an index value of 0.34-0.67 and high landslide hazard with an index value of 0.67-1.0. In 2016, Situjuah Limo Nagari Subdistrict was included in the moderate landslide hazard category with an index value of 0.34-0.67 covering 90% of the area and high landslide hazard categories with an index value of 0.68-1.0 covering 10% of an area. In 2017, Situjuah Limo Nagari Subdistrict was included in the moderate landslide hazard category with an index value of 0.34-0.67 covering 88% of the area and the high landslide hazard category with an index value of 0.68-1.0 covering 12% of an area. In 2018, Situjuah Limo Nagari Subdistrict was included in the moderate landslide hazard category with an index value of 0.34-0.67 covering 94% of the area and the high landslide hazard category with an index value of 0.68-1.0 covering 6% of an area. In 2019, Situjuah Limo Nagari Subdistrict was included in the moderate landslide hazard category with an index value of 0.34-0.67 covering 71% of the area and high landslide hazard category with an index value of 0.68-1.0 covering 29% of an area.